Atypical segmental multicystic dysplastic kidney with severe reflux in a newborn - Dorottya Balogh; Viktória Vass; Bálint Sulya; Ádám Fukász; Bálint Szmodics; András Kiss (Elsevier, 2022)
Segmental cases of multicystic dysplastic kidney (SMCDK) are rare and hard to diagnose, imaging characteristics are not evident. SMCDK can be presented with duplex collecting system, vesicoureteral reflux (VUR), pyeloureteric junction obstruction and orthotopic ureterocele. Typical cases are localized to the upper pole of a duplex collecting system. Atypical cases are rarely reported. We present an unique atypical SMCDK case, with unconventional disease manifestation to bring attention to the variable presentation of this rare disorder and to draw attention to differential diagnostic challenges of cystic kidney malformations.In our patient newborn screening abdominal ultrasound detected severe hydronephrosis and hydroureter of the lower pole of the right kidney. Dynamic renal scintigraphy and sonocystography confirmed duplication of both collecting systems and severe VUR in the right lower pole. Heminephrectomy was performed. The suspected diagnosis of atypical SMCDK was confirmed by histopathology. The patient recovered uneventfully.This unusual case of atypical SMCDK highlights the importance of considering the possibility of SMCDK in patients with partial kidney malformation or unusual appearance of congenital kidney disease.